Research Progress on Mechanism of Action of Vascular Endothelial Cells in Autologous Arteriovenous Fistula Stenosis - Li, Hang; Zhao, Yanlong (Journal of Contemporary Medical Practice, 2025)
At present, arteriovenous fistula is the preferred vascular access for hemodialysis patients. In clinical practice, arteriovenous fistula is often narrow, in which vascular endothelial cells play an important role. This paper introduces the mechanism of arteriovenous fistula stenosis, the function of endothelial cells, the common injury mechanism, and the relationship between endothelial cells and endometrial hyperplasia, and further discusses the role of vascular endothelial cells in the occurrence and development of arteriovenous fistula stenosis, in order to provide new ideas for improving the prognosis of arteriovenous fistula stenosis by intervening vascular endothelial cells.